Is religion necessary for morality? - Bahçekapili, Hasan G. (Religion, brain & behavior, 2017)
As a possible Hilbert question in the scientific study of religion, this article tries to explicate one specific relation between religion and morality: whether religion is necessary for morality. More specifically, how does the introduction of religion transform morality? The article operationalizes morality as normative and meta-ethical judgments and tries to specify ways to answer the question at three different levels: phylogenetic, historical, and ontogenetic. At the phylogenetic level, the possibility of moral judgments in non-human (and non-religious) primates is explored. At the historical level, a way to explore the question of how the rise of religions with Big Gods transformed morality is proposed. At the ontogenetic level, the effect of religious training in childhood and a shift to non-belief in adulthood on morality is explored. Finally, investigating the reverse causal influence (i.e., moral beliefs transforming religiosity) and the role of religious rituals (rather than religious beliefs) on morality are proposed as future directions.